Pengaruh Harga, Proses Dan Tempat Terhadap Kepuasan Konsumen Pada Percetakan CV. Karya Sehati Jaya Medan - Samuel Tenang Ukur Ardianta Ginting; Charisma Kuriata Ginting; Nora Adiya Sitanggang; Ade Windari (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2025)
In a rapidly changing global economy, businesses are planning and implementing creative and innovative businesses that satisfy consumers. The increasing demand for printing, photocopying, merchandise, and other products and services has forced companies to adjust prices, processes, and locations to meet customer satisfaction. The purpose of this study is to determine the influence of the independent variables (X) on price, process, and location, and the dependent variable (Y) on customer satisfaction. The method used is quantitative descriptive analysis. The results of the multiple correlation (R) test indicate that each increase in the independent variable will increase the dependent variable. The results of the multiple coefficient of determination test indicate that the independent variables collectively influence the dependent variable, while the remaining variables are influenced by other variables. The partial coefficient test reveals the most dominant independent variable. The quantitative research method tests the theory of variable measurement using numbers and statistical data analysis using SPSS software. The target output is published in the Journal Online System. Based on this, the researcher chose the research title "The Influence of Price, Process, and Location on Customer Satisfaction at CV. Karya Sehati Jaya Printing, Medan.